Comparison of intestinal expression of the apical sodium‐dependent bile acid transporter between dogs with and without chronic inflammatory enteropathy. (12th October 2018) - Giaretta, Paula R.; Rech, Raquel R.; Guard, Blake C.; Blake, Amanda B.; Blick, Anna K.; Steiner, Jörg M.; Lidbury, Jonathan A.; Cook, Audrey K.; Hanifeh, Mohsen; Spillmann, Thomas; Kilpinen, Susanne; Syrjä, Pernilla; et al.
Abstract : Background: Intestinal absorption of bile acids is mediated by the apical sodium‐dependent bile acid transporter (ASBT). Fecal bile acid dysmetabolism has been reported in dogs with chronic inflammatory enteropathy (CIE). Objective: Characterization of ASBT distribution along the intestinal tract of control dogs and comparison to dogs with CIE. Animals: Twenty‐four dogs with CIE and 11 control dogs. Methods: The ASBT mRNA and protein expression were assessed using RNA in situ hybridization and immunohistochemistry, respectively. The concentrations of fecal bile acids were measured by gas chromatography‐mass spectrometry. The fecal microbiota dysbiosis index was assessed with a quantitative polymerase chain reaction panel. Results: In control dogs, ASBT mRNA expression was observed in enterocytes in all analyzed intestinal segments, with highest expression in the ileum. The ASBT protein expression was restricted to enterocytes in the ileum, cecum, and colon. Dogs with CIE had significantly decreased expression of ASBT protein in the ileum ( P = .001), which was negatively correlated with histopathological score (ρ = −0.40; P corr = .049). Additionally, dogs with CIE had a significantly increased percentage of primary bile acids in feces compared to controls ( P = .04). The fecal dysbiosis index was significantly higher in dogs with CIE than in control dogs ( P = .01). Conclusions and Clinical Importance: These findings indicate that ileal protein expression of ASBT is downregulated in dogs with CIE. This change may be linked to the inflammatory process, intestinal dysbiosis, and fecal bile acid dysmetabolism observed in these patients.